Habitat utilization of the Eurasian spoonbill (Platalea leucorodia) wintering in the Yancheng National Nature Reserve: relative importance of artificial habitats - Xu, Peng; Mao, Shenbo; Zhang, Shusong; Bempah, Godfred; Zhao, Yongqiang (Frontiers in Ecology and Evolution, 2024)
Coastal wetlands are among the most modified habitats because of the loss and degradation of tidal flats, resulting in a rapid decline in waterbirds migrating along flyways. Understanding the relative importance of multiple types of wetlands as habitats for waterbirds, and the factors influencing their utilization, could improve management effectiveness. During the wintering seasons of 2021-2022 and 2022-2023, we documented the distribution of Eurasian Spoonbills (Platalea leucorodia), a wetland specialist, in the Yancheng National Nature Reserve (YNNR), and quantified the surrounding environments as influencing factors to assess the relationship between their habitat use patterns and environmental characteristics. Our results showed that spoonbills inhabit Common Seepweed (Suaeda glauca) marshes, reed (Phragmites australis) ponds, aquaculture ponds, and agricultural channels. Although natural wetlands supported a greater number of spoonbills in the YNNR, spoonbills were able to forage in artificial wetlands. The environmental features where the spoonbills were distributed were found to influence their habitat use, and the most important factor was water depth, followed by species richness and vegetation cover. These results demonstrated that spoonbills relied on both natural and artificial wetlands in the core and buffer zones of the YNNR. Our research thus underlined that conservation interventions of natural and artificial wetlands, such as controlling the water depth and diminishing human activities, might maximize the effects of total conservation outcomes for the Eurasian Spoonbills, as well as for various coastal waterbirds with similar ecological requirements.